2008
DOI: 10.1111/j.1524-4741.2007.00556.x
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Fasciitis Following Modified Radical Mastectomy

Abstract: stromal component comprised loose-spindled cells with no cytologic atypia or mitotic activity. The majority of the stromal cells contained homogenously eosinophilic hyaline intracytoplasmic inclusions. Immunohistochemically the spindled stromal cells were positive for smooth muscle actin, vimentin, and desmin, and negative for S100 protein. The inclusion bodies were highlighted by smooth muscle actin (Fig. 2).This case was diagnosed as a benign Phyllodes tumor with intracytoplasmic inclusion bodies identical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…1,2 Shah et al 1 reported a case in a 50-year-old, black, type II diabetic and Keune et al 2 in a 47-year-old Caucasian. NF of the breast has also been reported in the literature in postmastectomy wounds, 3–5 associated with ulceration of the breast 6,7 and following core needle biopsy. 8…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…1,2 Shah et al 1 reported a case in a 50-year-old, black, type II diabetic and Keune et al 2 in a 47-year-old Caucasian. NF of the breast has also been reported in the literature in postmastectomy wounds, 3–5 associated with ulceration of the breast 6,7 and following core needle biopsy. 8…”
Section: Discussionmentioning
confidence: 87%
“…Consistent with NF in other regions of the body, NF of the breast is most commonly type I; 13,6,7 however, type II NF has also been described. 4,5,8 Type II diabetes has been implicated in two 1,5 out of the eight other case reports of NF of the breast and at least two of these patients were also obese; 3,5 however, one patient had no identified risk factors. 2…”
Section: Discussionmentioning
confidence: 99%
“…Type II NF, as in the case of our patient, is most common in young, previously healthy, and immunocompetent adults, and is more likely to occur without a clear precipitating factor . Among the 16 reported cases of breast NF, common risk factors include DM , history of an invasive breast procedure, and a history of breast cancer . Notably, however, no clear precipitating factor was identified in six reported cases .…”
Section: Discussionmentioning
confidence: 94%
“…Necrotizing fasciitis of the breast can be idiopathic [1,13] or secondary to other causes, i.e, following a needle core biopsy [14,15], elective total or partial mastectomy [7,[16][17][18][19], human bites [15], penetrating injury [20], anticoagulation therapy [21][22][23], topical belladonna application [24], in patients with puerperal sepsis [25], and breast tumors with mammary infarcts in pregnant patients [26,27]. Our literature search revealed that trauma, small trivial wounds, or even minor scratches can cause necrotizing fasciitis [28].…”
Section: Discussionmentioning
confidence: 99%